Draft Annual Plan (1970-71) Part-I Union Territory of Delhi - Planning Commission (Planning Commission, 1970)
For the preparation of purposeful development Plans for the Union Territory of Delhi, the following factors have to be kept in view: a) In view of its predominant urban character, this Territory has peculiar development problems. b) The population of Delhi has been increasing at a phenomenal rate, which is unparalleled in any city of the country.
Planning Department Delhi Administration